2002
DOI: 10.1002/joc.857
|View full text |Cite
|
Sign up to set email alerts
|

Historical changes in lake ice‐out dates as indicators of climate change in New England, 1850–2000

Glenn A. Hodgkins,
Ivan C. James,
Thomas G. Huntington

Abstract: Various studies have shown that changes over time in spring ice-out dates can be used as indicators of climate change. Ice-out dates from 29 lakes in New England (USA) with 64 to 163 years of record were assembled and analysed for this study. Ice-out dates have become significantly earlier in New England since the 1800s. Changes in ice-out dates between 1850 and 2000 were 9 days and 16 days in the northern/mountainous and southern regions of New England respectively. The changes in the ice-out data over time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 23 publications
(25 reference statements)
8
77
0
4
Order By: Relevance
“…4) are consistent with changes found by others (Livingstone 1997(Livingstone , 1999Magnuson et al 2000;Hodgkins et al 2002;Weyhenmeyer et al 2005;Duguay et al 2006;Korhonen 2006;Livingstone et al 2010). The mean trends in measures of lake ice phenology were consistently in the direction of later freezes, earlier breakups, and shorter durations in each of the three time periods (Table 1) although some trends were not significant based on Theil-Sen slopes or a less powerful test that eliminated spatial autocorrelation.…”
Section: Discussionsupporting
confidence: 94%
“…4) are consistent with changes found by others (Livingstone 1997(Livingstone , 1999Magnuson et al 2000;Hodgkins et al 2002;Weyhenmeyer et al 2005;Duguay et al 2006;Korhonen 2006;Livingstone et al 2010). The mean trends in measures of lake ice phenology were consistently in the direction of later freezes, earlier breakups, and shorter durations in each of the three time periods (Table 1) although some trends were not significant based on Theil-Sen slopes or a less powerful test that eliminated spatial autocorrelation.…”
Section: Discussionsupporting
confidence: 94%
“…The records of the last two centuries of ice break-up dates on the rivers in the Northern Hemisphere provide consistent evidence of later freezing and earlier break-up (Magnuson et al 2000). Several studies have analyzed ice regime trends for inland waters, since easily identifiable parameters describing ice break-up have been recorded for a long period of time (Beltaos 1997;Benson et al 2000;Likens 2000;Arai 2000;Hodgkins et al 2002). These studies have clearly shown long-term changes in climate, and have also argued that natural processes and the ice regime of surface waters in the Northern Europe are related to the changes in NAO (Yoo and D'Odorico 2002).…”
Section: Introductionmentioning
confidence: 91%
“…Although coherent across the state, the records show some variation in the timing of major changes. Starting in the late 1800s, ice-out dates occurred progressively earlier for Sebago Lake, and are about 30 days earlier (Hodgkins et al 2002), with the greatest decline between 1875 and 1930 ( Fig. 2).…”
Section: Study Sitementioning
confidence: 99%
“…All three lakes experienced the same regional declines in wind speed (Pryor et al 2009) and progressively earlier ice-out dates (Hodgkins et al 2002), but differ in morphometry. This allowed us to assess whether within-lake processes in these large lakes influence the links between climate and diatom responses.…”
Section: Introductionmentioning
confidence: 99%